The local agenda 21 (LA21) implementation in Miri city council - Siti Fatimah Sikandar (Kulliyyah of Economics and Management Sciences, International islamic University Malaysia, 2015)
Sustainability development is an important aspect in present globalization era. There are three elements relating to sustainability development; which are economic, social, and environment. Local Agenda 21 (LA21) is a framework without binding for action to accomplish sustainable development outputs from the 1992 United Nations Conference on Environment and Development. The LA21 had been implemented in Malaysia since the year 2000. Four local authorities are involved in the pilot project. The local authorities are Petaling Jaya City Council (MPPJ), Kerian District Council, Kuantan Municipal Council, and Miri City Council (MCC). This study is carried out in the MCC as a case study for the implementation of LA21 which represents Malaysia local authority. The purpose of this study is to document the implementation of LA21 in Miri. The studies also looks at the activities carried out by the MCC, to find out the challenges relating to the implementation of LA21 in Miri, and to evaluate which stakeholder group that are given the priority in the LA21 implementation activities in Miri and also the attributes of the stakeholders empowerment. The data are collected through interviews and document analysis. It is found that in Miri, the activities for the LA21 implementation are more focus on the environmental activities. The research findings reveals that there are four challenges relating to LA21 implementation in Miri which are the lack of the participation and support from the community, funding or financial resource, the lack of local authority management support, and human resource policies. The finding also reveals that there is certain stakeholder prioritization, empowerment, and attributes involved in the LA21 implementation in Miri.